2021
DOI: 10.31235/osf.io/jv56d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coping With Digital Market Re-Organization: How the Hotel Industry Strategically Responds to Digital Platform Power

Abstract: How do organizations in a sector where powerful platforms have emerged cope with the new constraints and opportunities that platforms induce? A growing number of studies highlights the power of digital platforms to re-organize markets and thereby create new forms of dependence. But there are also indications that organizations are capable of countering platform power especially by demanding their regulation. This paper expands this view to investigate also strategies at the organizational level. It draws on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The topic of digital distribution of hotel and restaurant business services covers research of digital markets, digital technologies, and distribution of services. "A growing number of studies highlights the power of digital platforms to re-organize markets and thereby create new forms of dependence" (Balsiger et al, 2021). Digital markets have their own characteristics and "include all kinds of trading using the Internet for product search, purchasing, and payment" (Overby & Audestad, 2021b) and have long been a zone of "blue ocean" strategies (Carton, 2017; Mesut, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of digital distribution of hotel and restaurant business services covers research of digital markets, digital technologies, and distribution of services. "A growing number of studies highlights the power of digital platforms to re-organize markets and thereby create new forms of dependence" (Balsiger et al, 2021). Digital markets have their own characteristics and "include all kinds of trading using the Internet for product search, purchasing, and payment" (Overby & Audestad, 2021b) and have long been a zone of "blue ocean" strategies (Carton, 2017; Mesut, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is indicated that "the prospects for Internet use and consumption associated with the hotel sector will increase even more in the coming years" (Cruz, 2003, p. 105). Currently, "digitalization brings the challenge to hotels' work process" (Buer, 2019, p. 6), and "the hotel industry strategically responds to digital platform power" (Balsiger et al, 2021). In the post-pandemic period, digitalization will become one of the main strategic concepts in the tourism and hotel business (Melnychenko et al, 2020;Mazaraki et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%